KOORDINASI DALAM PENERAPAN SISTEM ZONASI SEKOLAH ANTARA DINAS PENDIDIKAN DAN DINAS CATATAN SIPIL KOTA MAKASSAR (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to analyze and describe the coordination in the implementation of the school zoning system between the Education Office and the Makassar City Civil Registry Office. This research uses a case study type of qualitative research. The research data were collected through interviews, observations, and documentation studies. The results of the coordination research in the application of the zoning system between the Education Office and the Makassar City Civil Registry Office show that from the aspect of (1) The unit of action from the Education Office trying to improve population data is also carried out by the civil registry office where the registration process no longer requires the public to legalize population administration in civil registry office and delegated to the village government. (2) Communication also makes updates to the application system where to find out the zoning of prospective students who will register, it is enough to enter their NIK or population data in the requested column and automatically the location or zone can be directly directed through the application. (3) Division of Work The education office has issued guidelines and technical guidelines for the implementation of PDDB in accordance with the direction of the ministry of education, while the civil registry service has updated population data which is synchronized with the PPDB application. (4) The discipline of the apparatus involved in the PPDB work unit is required to fill in the facts of integrity relating to the readiness of the committee in implementing the PPDB.